Use of Clinical Disease Activity Index Score for Assessment of Disease Activity in Rheumatoid Arthritis Patients: An Indian Experience. (6th December 2011) - Singh, H.; Kumar, H.; Handa, R.; Talapatra, P.; Ray, S.; Gupta, V.
Abstract : Introduction . Serial objective assessment of disease activity in Rheumatoid Arthritis (RA) is imperative to achieve remission. The CDAI score appears more practical than DAS-28 in routine assessment of disease activity in RA patients. Objective . To evaluate correlation and agreement of the DAS-28 with CDAI in RA patients. Methods . A total of 200 patients of RA were evaluated by DAS-28 and CDAI and divided into 4 categories of disease activity i.e. Group-I: Remission (DAS-28 < 2.6; CDAI < 2.8), Group II: Low disease activity (DAS-28 = 2.6–3.2; CDAI = 2.8–10), Group III: Moderate disease activity (DAS-28 = 3.2– 5.1; CDAI = 10–22), Group IV: High disease activity (DAS-28 > 5.1; CDAI > 22). DAS-28 was compared to CDAI in each group using spearman correlation coefficient and kappa statistics. Results . Group I shows mean DAS-28 of1.99 ± 0.38 ; mean CDAI of0.90 ± 0.65, (P = 0.0001). Group II shows mean DAS-28 of3.04 ± 0.17 ; mean CDAI of6.45 ± 02.35, (P = 0.0001). Group III shows mean DAS-28 of4.25 ± 0.58 ; mean CDAI of16.46 ± 3.31 (P < 0.0001). Group IV shows mean DAS-28 of6.38 ± 0.87 ; mean CDAI of38.56 ± 11.88 (P < 0.0001). Kappa statistics (κ ) of the above comparison was 0.533. Conclusion . Our findings indicate that CDAI—a composite score that employs only clinical variables and omits assessment of Acute Phase Reactant (APR), has moderate to good correlation (Kappa value = 0.533) to DAS-28 for assessment of disease activity in RA patients.